Atributos químicos e biológicos de um Antropossolo sob utilização de água residuária tratada no Semiárido - Meireles, Denisvaldo Artur de (2019)
Water scarcity grows by the day, especially in the semiarid regions. As a result, the amount of groundwater used in agriculture is strictly limited, and it has become necessary to explore alternative sources of water. The objective of the present study was to evaluate the potential of treated wastewater in the recovery of fertility of an anthroposol and in the vegetative growth of forage and forest palm, as well as to determine the basal respiration, carbon of the microbial biomass and metabolic quotient of an anthroposol year with wastewater irrigation. The experiment was conducted in a 780m2 area in Paraíba Semiarid in a randomized block design with ten replications, three plant species and three treatments, corresponding to the type and volume of water used (T1 = 500 ml of water supply -AA , T2 = 500 ml of wastewater -AR , T3 = 1000 ml of wastewater -AR). The experiment was carried out in an agroforestry system with 1560 forage palm rackets: Mexican elephant ear ( Opuntia tuna ) and 195 seedlings of 2 forest species : Sabiá (Mimosa ceasalpinifolea Benth ) and Aroeira Branca ( Myracrodruon urundeuva Allmanha) planted in double row. Biometric variables were investigated in the forage palm and in the sabiá forest species. Soil was collected before and after irrigation and analyzed for chemical and biological attributes. In the chemical parameters of the soil, significant contrasts were observed only for pH, Organic Matter, CTC, and Sum of Bases. The pH Initial was classified as neutral, changing to a weak acidity after treatment application, being more relevant between the initial soil pH (pH 6.9) and the addition 500 ml AA weekly (pH 5.9 ). MOS contents increased significantly after AR use. Regarding CTC, it was found that the plots that received the RA doses presented the highest values, when compared to the plots that received AA. Regarding the vegetative growth, the treatment with 1000 ml of wastewater weekly, responded better in all variables of forage palm , where it obtained a final average of 36.2 cm. The basal respiration of the soil did not respond significantly to the treatments, the biomass carbon was higher in the area with forest species, however the metabolic quotient had no significant differences between treatments. Regarding the chemical properties of the soil, the wastewater had greater influences on soil pH and organic matter, showing to be a promising alternative for the recovery of the productive capacity of the soil, mainly by the increase of the MOS. The effect on forage palm growth was greater on the 1000 ml treated wastewater slide, the 500 ml and 1000 ml week treated wastewater slides did not promote differences in the height and diameter growth of the thrush. The area under forest vegetation stood out in relation to the palm, possibly due to the larger contribution of organic residues from the plant itself, serving as a source of nutrients to the soil microbiota. Soil biological properties: basal respiration, biomass carbon and metabolic quotient were not directly influenced by the treatments.